Lomustine with or without reirradiation for first progression of glioblastoma, LEGATO, EORTC-2227-BTG: study protocol for a randomized phase III study - Preusser, Matthias; Kazda, Tomáš; Le Rhun, Emilie; Sahm, Felix; Smits, Marion; Gempt, Jens; Koekkoek, Johan Af; Monti, Angelo F; Csanadi, Marcell; Pitter, János György; Bulbek, Helen; Fournier, Beatrice; et al. (Trials, 2024)
BACKGROUND: Chemotherapy with lomustine is widely considered as standard treatment option for progressive glioblastoma. The value of adding radiotherapy to second-line chemotherapy is not known. METHODS: EORTC-2227-BTG (LEGATO, NCT05904119) is an investigator-initiated, pragmatic (PRECIS-2 score: 34 out of 45), randomized, multicenter phase III trial in patients with first progression of glioblastoma. A total of 411 patients will be randomized in a 1:1 ratio to lomustine (110 mg/m2 every 6 weeks) or lomustine (110 mg/m2 every 6weeks) plus radiotherapy (35 Gy in 10 fractions). Main eligibility criteria include histologic confirmation of glioblastoma, isocitrate dehydrogenase gene (IDH) wild-type per WHO 2021 classification, first progression at least 6 months after the end of prior radiotherapy, radiologically measurable disease according to RANO criteria with a maximum tumor diameter of 5 cm, and WHO performance status of 0-2. The primary efficacy endpoint is overall survival (OS) and secondary endpoints include progression-free survival, response rate, neurocognitive function, health-related quality of life, and health economic parameters. LEGATO is funded by the European Union's Horizon Europe Research program, was activated in March 2024 and will enroll patients in 43 sites in 11 countries across Europe with study completion projected in 2028. DISCUSSION: EORTC-2227-BTG (LEGATO) is a publicly funded pragmatic phase III trial designed to clarify the efficacy of adding reirradiation to chemotherapy with lomustine for the treatment of patients with first progression of glioblastoma. TRIAL REGISTRATION: ClinicalTrials.gov NCT05904119. Registered before start of inclusion, 23 May 2023.
Keywords: Randomized Controlled Trials as Topic; Antineoplastic Agents, Alkylating; Progression; LEGATO; Quality of Life; doba přežití bez progrese choroby; Reirradiation; Multicenter Studies as Topic; časové faktory; kvalita života; Time Factors; nádory mozku; lidé; klinické zkoušky, fáze III jako téma; glioblastom; Glioblastoma; multicentrické studie jako téma; progrese nemoci; lomustin; Disease Progression; Randomized controlled trial; Brain Neoplasms; randomizované kontrolované studie jako téma; chemoradioterapie; pragmatické klinické studie jako téma; Clinical Trials, Phase III as Topic; Lomustine; Pragmatic Clinical Trials as Topic; alkylační protinádorové látky; Progression-Free Survival; Chemoradiotherapy; Humans